Fastball pitching performance only slightly decreases after mobility impediment of the pelvis and trunk—Do (catch-up) compensation strategies come into play? - Leenen, A. J. R.; Trigt, Bart van; Hoozemans, M. J. M.; Veeger, H. E. J. (Frontiers in Sports and Active Living, 2022)
Background Baseball pitching performance can be mechanically explained by the summation of speed principle and the principle of optimal coordination of partial momenta. Impeding optimal energy generation or transfer by or between the pelvis and trunk segments could provide valuable insight into possible compensation or catch-up mechanisms that may manifest themselves based on these principles. Aim The aim of the present study was to explore the effects of experimentally impeding the mobility of and between the pelvis and trunk segments (1) on ball speed and mechanical peak joint power, and (2) on mechanical peak load of the elbow and shoulder joints at maximal external rotation (MER) during fastball pitching. Methods Eleven elite baseball pitchers (mean age 17.4, SD 2.2 years; mean pitching experience 8.9, SD 3.0 years) were instructed to throw at least 15 fastballs as fast and accurately as possible under two conditions. One condition involved impeding the mobility of the pelvis and trunk segments to hamper their ability to rotate independently, which consequently should affect the separation time, defined as the time interval between the pelvis and trunk peak angular velocities. In the other condition, pitchers threw unimpeded. Ball speed, mechanical peak joint power and peak net moment of the elbow and shoulder at MER were compared between conditions using Generalized Estimating Equations (GEE). Results In the impeded pitching condition, the mean difference of the separation time was 12.4 milliseconds [95% CI (4.0, 20.7)] and for ball speed 0.6 mph [95% CI (0.2, 0.9)] lower compared to the unimpeded condition. Only the peak pelvic angular velocity, in addition to the trunk, upper arm and forearm, was 45 deg/s [95% CI (24, 66)] higher impeded condition. The mean differences of the joint power and net moments at the shoulder and elbow did not reach statistical significance. Conclusion In elite adolescent baseball, the observed pitching performance after experimentally impeding pelvic and trunk mobility undermines a potential distal catch-up strategy based on the summation of speed principle. The increased peak pelvic angular velocity may indicate a compensation strategy following the optimal coordination of partial momenta principle to practically maintain pitching performance.